DEVELOPMENT OF AN ONTOLOGICAL MODEL OF SYNTACTIC RULES OF SIMPLE SENTENCES OF TURKISH LANGUAGE - Zhetkenbay Л; Razakhova Б.Ш; Yergesh Б; Mukanova А.С (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This article describes the syntactic rules of sentences in Turkish language and presented its tree components as well by means of formal grammars Chomsky. At the same time, an ontological model of syntactic rules of simple sentences of the Turkish language is constructed, taking into account its semantics. The proposed ontological models use terms from the unified metalanguage UniTurk to denote syntactic categories and concepts. The results of this work can be used to solve NLP tasks, for example, in the systems of knowledge, information retrieval, question and answering systems, in machine translation, automatic summarization of Turkish texts, as well as in the reference and training systems, moreover, in building the ontological model of syntax rules of Turkic languages and is planned to use.